Genome-wide identification and comprehensive analysis of the COI1 gene family in Medicago sativa - Chen, Fangqi; Wang, Luran; Jia, Ruifang; Zhao, Jun; Lin, Kejian; Zhao, Qing; Chen, Zhengqiang; Zhang, Yuanyuan (Frontiers in Plant Science, 2025)
COI1 (CORONATINE INSENSITIVE) is a central regulator of plant defense against biotic stresses, yet its family members remain uncharacterized in the globally important forage crop alfalfa (Medicago sativa L.). Here, we identified 32 MsCOI1 genes, which were phylogenetically classified into four subfamilies (I–IV). The four subfamilies each contain 5, 6, 9, and 12 MsCOI1 genes, respectively. Structural analysis revealed conserved three-exon architecture and six critical motifs, with Motif 3 exclusively absent in Subfamily IV. Promoter cis-element profiling showed enrichment in stress-responsive elements: 93.8% contained ABRE (abscisic acid response), 68.8% harbored MeJA-responsive elements, and 50% possessed TC-rich repeats (defense/stress response). Expression dynamics demonstrated tissue specificity (e.g., MsCOI1-24/25/26 in nodules/roots) and hormone responsiveness (40.6% induced by MeJA/ABA). Crucially, six of eight tested MsCOI1s were upregulated during Alfamovirus AMV (commonly known as Alfalfa mosaic virus, AMV) infection. However, MsCOI1–8 was significantly inhibited at 5 dpi, indicating that the virus manipulates the COI1-mediated plant response. This study provides the first comprehensive resource of MsCOI1 genes for enhancing viral resistance in alfalfa breeding.